Magnetic resonance-guided focused ultrasound for the treatment of tremor. (3rd October 2022) - Yamamoto, Kazuaki; Sarica, Can; Loh, Aaron; Vetkas, Artur; Samuel, Nardin; Milano, Vanessa; Zemmar, Ajmal; Germann, Jürgen; Cheyuo, Cletus; Boutet, Alexandre; Elias, Gavin JB; Ito, Hisashi; et al.
ABSTRACT: Introduction: Magnetic resonance-guided focused ultrasound (MRgFUS) is an emerging treatment for tremor and other movement disorders. An incisionless therapy, it is becoming increasingly common worldwide. However, given MRgFUS' relative novelty, there remain limited data on its benefits and adverse effects. Areas covered: We review the current state of evidence of MRgFUS for tremor, highlight its challenges, and discuss future perspectives. Expert opinion: Essential tremor (ET) has been the major indication for MRgFUS since a milestone randomized controlled trial (RCT) in 2016, with substantial evidence attesting to the efficacy and acceptable safety profile of this treatment. Patients with other tremor etiologies are also being treated with MRgFUS, with studies – including an RCT – suggesting parkinsonian tremor in particular responds well to this intervention. Additionally, targets other than the ventral intermediate nucleus, such as the subthalamic nucleus and internal segment of the globus pallidus, have been reported to improve parkinsonian symptoms beyond tremor, including rigidity and bradykinesia. Although MRgFUS is encumbered by certain unique technical challenges, it nevertheless offers significant advantages compared to alternative neurosurgical interventions for tremor. The fast-growing interest in this treatment modality will likely lead to further scientific and technological advancements that could optimize and expand its therapeutic potential.